Beam splitting in chiral nematic liquid crystals - Sala, Filip (Photonics Letters of Poland, 2018)
By lunching the beam into the chiral nematic liquid crystals it is possible to achieve a non-diffractive beam similar to a soliton. This effect is caused by the molecular reorientation i.e. nonlinear response of the material forming the areas of higher refractive index. Diffraction is suppressed by the focusing effect. For appropriate launching conditions it is also possible to achieve a beam which splits into two or more separate beams. Such phenomenon is discussed in this article and analyzed theoretical. To model this effect Fully Vectorial Beam Propagation Method coupled with the Frank-Oseen elastic theory is used. Simulations are performed for various input beam powers, widths, polarization angles and launching positions. Full Text: PDF References G. Assanto and M. A. Karpierz, "Nematicons: self-localised beams in nematic liquid crystals", Liq. Cryst. 36, 1161–1172 (2009) CrossRef G. Assanto, Nematicons: Spatial Optical Solitons in Nematic Liquid Crystals, John Wiley & Sons Inc. Hoboken, New Jersey (2013) DirectLink A. Piccardi, A. Alberucci, U. Bortolozzo, S. Residori, and G. Assanto, "Soliton gating and switching in liquid crystal light valve", Appl. Phys. Lett. 96, 071104 (2010). CrossRef D. Melo, I. Fernandes, F. Moraes, S. Fumeron, and E. Pereira, "Thermal diode made by nematic liquid crystal", Phys. Lett. A 380, 3121 – 3127 (2016). CrossRef U. Laudyn, M. Kwaśny, F. A. Sala, M. A. Karpierz, N. F. Smyth, G. Assanto, "Curved optical solitons subject to transverse acceleration in reorientational soft matter", Sci. Rep. 7, 12385 (2017) CrossRef M. Kwaśny, U. A. Laudyn, F. A. Sala, A. Alberucci, M. A. Karpierz, G. Assanto, "Self-guided beams in low-birefringence nematic liquid crystals", Phys. Rev. A 86, 013824 (2012) CrossRef F. A. Sala, M. M. Sala-Tefelska, "Optical steering of mutual capacitance in a nematic liquid crystal cell", J. Opt. Soc. Am. B. 35, 133-139 (2018) CrossRef U. A. Laudyn, A. Piccardi, M. Kwasny, M. A. Karpierz, G. Assanto, "Thermo-optic soliton routing in nematic liquid crystals", Opt. Lett. 43, 2296-2299 (2018) CrossRef F. A. Sala, M. M. Sala-Tefelska, M. J. Bujok, J. "Influence of temperature diffusion on molecular reorientation in nematic liquid crystals", Nonlinear Opt. Phys. Mater. 27, 1850011 (2018) CrossRef I-C Khoo Liquid crystals John Wiley & Sons, Inc (2007) DirectLink P. G. de Gennes, J. Prost, The Physics of Liquid Crystals, Clarendon Press (1995) DirectLink U. A. Laudyn, P. S. Jung, M. A. Karpierz, G. Assanto, "Quasi two-dimensional astigmatic solitons in soft chiral metastructures", Sci. Rep. 6, 22923 (2016) CrossRef J. Beeckman, A. Madani, P. J. M. Vanbrabant, P. Henneaux, S-P. Gorza, M. Haelterman, "Switching and intrinsic position bistability of soliton beams in chiral nematic liquid crystals", Phys. Rev. A 83, 033832 (2011) CrossRef A. Madani, J. Beeckman, K. Neyts, "An experimental observation of a spatial optical soliton beam and self splitting of beam into two soliton beams in chiral nematic liquid crystal", Opt. Commun. 298–299, 222-226, (2013) CrossRef G. D. Ziogos, E. E. Kriezis, "Modeling light propagation in liquid crystal devices with a 3-D full-vector finite-element beam propagation method", Opt. Quant. Electron 40, 10 (2008) CrossRef F. A. Sala, M. A. Karpierz, "Chiral and nonchiral nematic liquid-crystal reorientation induced by inhomogeneous electric fields", J. Opt. Soc. Am. B 29, 1465-1472 (2012) CrossRef F. A. Sala, M. A. Karpierz, "Modeling of molecular reorientation and beam propagation in chiral and non-chiral nematic liquid crystals", Opt. Express 20, 13923-13938 (2012) CrossRef F. A. Sala, "Design of false color palettes for grayscale reproduction", Displays, 46, 9-15 (2017) CrossRef